2021
DOI: 10.24042/ajpm.v12i2.9874
|View full text |Cite
|
Sign up to set email alerts
|

Error analysis of prospective mathematics teachers in solving of applying radian measurement problem in trigonometry courses

Abstract: This research aims to describe the mistakes of the prospective teachers in solving the application of radian measurement problems and their causes. This type of research is qualitative descriptive research with a case study approach. The types of data collection in this research consisted of the results of the subject's work and transcripts of interviews with research subjects. By following the type of data, this research instrument consists of one question about the problem of applying radian measurement and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…Thus, the chances of obtaining correct solutions are higher in learners who can make feature connections. These findings are contrary to Setiawan and Surahmat (2021) who found that participants fail to pay attention to the information given in the trigonometric problem. Participants were able to pay attention to every detail of the information given.…”
Section: Feature Connectionscontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, the chances of obtaining correct solutions are higher in learners who can make feature connections. These findings are contrary to Setiawan and Surahmat (2021) who found that participants fail to pay attention to the information given in the trigonometric problem. Participants were able to pay attention to every detail of the information given.…”
Section: Feature Connectionscontrasting
confidence: 99%
“…For example, Marufi et al (2022) found out that learners experience challenges in comprehending trigonometric symbols and language, using correct algorithms, and retrieving appropriate prior knowledge. For Setiawan and Surahmat (2021), learners encounter the challenge of comprehending and extracting information from 2D trigonometric problems. This contributes to learners committing procedural errors (Nanmumpuni & Retnawati, 2021).…”
mentioning
confidence: 99%
“…However, the change in learning from what was originally carried out face-to-face to online learning hurt some students. The results of the research show that in online learning, students experience conceptual misunderstandings, principle misunderstandings, and factual misunderstandings (Y. E. Setiawan, 2022; Y. E. Setiawan & Surahmat, 2021). Various problems also arise in online learning, including difficulty adapting to online learning, lack of student understanding, saturation occurs in online learning, and limited interaction between teachers and students, resulting in decreased student understanding of the material being studied.…”
Section: Introductionmentioning
confidence: 98%
“…Even the results of the study also show that a creative person can find effective ways to solve mathematical problems [14]- [16]and can solve problems with various representations [17]. Meanwhile, students who tend to be uncreative will get stuck in errors in solving math problems [18], [19]. Creativity in this study is defined as an effort to find new alternative solutions in solving mathematical problems [20]- [22].…”
Section: Introductionmentioning
confidence: 99%